Sequestrate syndrome in Bondarzewia guaitecasensis (Fungi, Basidiomycota)? The case of Hybogaster giganteus revisited - Palfner, Götz; Galleguillos, Felipe; Arnold, Norbert; Casanova-Katny, Angélica; Horak, Egon (Phytotaxa, 2020)
Based on comparison of molecular, morphological and ecological data, we propose that Hybogaster giganteus Singer, a parasitic basidiomycete on stem bases and coarse roots of Nothofagus in Chile, is conspecifically related to the sympatric Bondarzewia guaitecasensis. According to our concept, H. giganteus is representing a sequestrate form of the latter and is hence recombined and formally described as Bondarzewia guaitecasensis f. gigantea; we further discuss the evidence that its sequestrate morphology may provide higher resistance to drought stress in early autumn, extending the sporulation season of the species.